Environmental Ergonomic Analysis: Understanding Noise Effects on Security and Comfort - Ridwan Gucci, Dinda Okta Dwiyanti; Nalendra, Muhammad Adi Sukma; Ramadhani, Fauziah Fatma (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
In activities production PT. XYZ has several forms of production processes. It is a grinding process, which has the potential to give rise to noise coming from the tools used during the production process. The continuous noise produced can damage healthy hearing workers. To know the noise level produced during the grinding process on module 04 and module 05 of the Santos project and calculate the recommended time When exposed to noise. Data collection will use a sound level meter to gauge noise. Data calculations using distribution frequency and counting level noise equivalent ( Leq ) obtain point noise on Dilinta Sembiring and Saiful above the Threshold Limit Value (NAV), namely 86.87 dBA and 85.35 dBA. Calculated exposure time use method NIOSH recommends that Crossed Sembiring can work for 5 hours 19 minutes and Saiful for 7 hours 37 minutes. If No, use PPE when exposed continuously. Keywords: Ergonomics Environment, Noise, Grinding, NOISH